The Self-Internationalization Model (SIM) versus Conventional Internationalization Models (CIMs) of the institutions of higher education: A preliminary insight from management perspectives - Khan, Mohammad Ayub; Noam, Ebner (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
Institutions of higher education increasingly engage in internationalization efforts for a variety of reasons. The collection of practices these institutions engage in, which can be called conventional internationalization models (CIM), primarily focus on centralized and institutionalized efforts. This paper reviews typical aspects of CIM, noting their benefits while also spotlighting the costs they entail and the open spaces they leave. The paper then introduces the self-internationalization model (SIM) as a complement and a supplement to CIM. SIM offers a less centralized approach to internationalization, focusing instead on individual initiatives taken by faculty, academic managers, and students. This paper explains the functional aspects of SIM and its comparative advantages and disadvantages vis-à-vis CIM. Furthermore, it provides guidelines for the design and implementation of comprehensive, innovative, flexible, and dynamic internationalization models combining SIM and CIM in a manner that is suitable, convenient, affordable, and beneficial for all stakeholders in higher education institutions.